MANAJEMEN PENGELOLAAN BANK SAMPAH - Latifah, Eny; Abdullah, Rudi (JITAA : Journal Of International Taxation, Accounting And Auditing, 2022)
The aim of this research is to determine the management of Waste Bank management. The research method is qualitative with a case study type. The results of the research are that waste bank management includes: first, planning: there are three plans, short term (increasing the number of members and compiling reports), medium term (optimizing reuse activities) and long term (collaborating with other institutions). Second, Organizing (organizing) consists of: Prosperous Waste Bank administrators carrying out tasks according to their respective fields and duties. Third, Actuating (implementation): Sejahtera Waste Bank implements a waste management program by applying the 3 R principles (reduce, reuse and recycle). and carrying out member savings activities as well as implementing a biopore hole creation program. And Fourth, Controlling: Prosperous Waste Bank carries out regular evaluations of waste bank programs.